Techno-economic analysis for a 100% renewable hybrid energy systems integration in a research facility in Morocco - Noure elhouda Choukri; Samir Touili; Abdellatif Azzaoui; Ahmed Alami Merrouni (iScience)
Summary: The objective of this study is to assess the optimal design of hybrid renewable energy systems (HRES) to achieve a 100% energy supply for a research institute located in mid-south Morocco. Using high-precision meteorological data and HOMER software simulations, and optimizing of various combinations of photovoltaic (PV) solar panels, wind turbines, biomass generators, and battery storage systems were done. Nine different scenarios were analyzed to identify the most cost-effective and technically viable system to meet the institute’s energy demands. Results show that the scenario including PV/biomass/battery combination provides the optimal solution to meet 100% energy demand from both technical and economic point of view with an LCOE of 0.33US$ and a total share of solar energy of 83.3%. These results are of significant importance as they offer valuable insights into the most suitable technologies and combinations for achieving a 100% green energy supply to Moroccan governmental organizations.